Strain-rate sensitivity of brittle deformation and removal mechanisms of monocrystalline 3C–SiC induced by nano cutting process - Binbin Meng; Chen Li (Journal of Materials Research and Technology, 2023)
In this work, the dynamic crack propagation mechanism of 3C–SiC at the micro-scale and the influence mechanism of the strain rate effect are studied, and the deformation mechanism under different strain rate is deeply analyzed. These simulations show many new phenomena, such as crack nucleation, deflection and arrest, defect accumulation and evolution near crack, strain rate effect on material deformation and removal. When the cutting velocity is equal to 5 m/s, the deformation mode of 3C–SiC is mainly sliding deformation, and the chip is separated from the matrix in the form of massive slump. When the cutting velocity reaches 500 m/s, the plastic deformation mode of the material in the machining region is the same, but the dislocation density is significantly reduced, and the material removal mode is transformed into a pure fracture mode. The brittle removal mode of monocrystalline SiC is closely related to the strain rate. The results will not only enhance the understanding the strain rate sensitivity of the damage evolution and removal behaviors of monocrystalline 3C–SiC involved at nano- and micro-scales, but also provide a theoretical guidance for optimizing process parameters during the SPDT process of monocrystalline 3C–SiC.